SPECIAL OMBUDSMEN WITH REFERENCE TO THE POSITION OF THE COMMISSIONER FOR INFORMATION OF PUBLIC IMPORTANCE AND PROTECTION OF PERSONAL DATA - Milan Rapajić; Dejan Logarušić (Pravo)
In addition to the expansion of general-type ombudsmen, it has been recognized that, for the protection of citizens’ rights, it is necessary to have the so-called specialized ombudsmen, who focus their activities on administrative oversight and the protection of citizens’ rights in specific areas of social life. Thus, there are public law ombudsmen of an external type, internal ombudsmen, and private law ombudsmen. This paper pays particular attention to the position of the Commissioner for Information of Public Importance and Protection of Personal Data in the Republic of Serbia, who is, in fact, a special public law ombudsman of an external type. The paper discusses this special ombudsman’s complex jurisdiction, which is defined by the Law on Free Access to Information of Public Importance and the Law on Personal Data Protection. The authors analyze the competences of this special type of ombudsmеn.